PENINGKATAN PENGETAHUAN TENTANG PENGEMBANGAN PRODUK OLAHAN KETELA MELALUI PERLOMBAAN HUT REPUBLIK INDONESIA PADA IBU-IBU KALIJERUK I DAN II - Andrean Emaputra; Ellyawan Setyo Arbintarso; Toto Rusianto; Endang Widuri Asih; Mega Inayati Rif`ah; Eka Sulistyaningsih; Dandung Junustisio Muktar; Davin Satria Nugraha (Abdimas Aswaja: Jurnal Pengabdian Masyarakat, 2026)
Currently, there is a growing trend of processed foods made from natural and healthy ingredients. One such ingredient is cassava, which provides good nutritional value. Additionally, this ingredient is tasty, affordable, and readily available in local communities. One of the residents of the Special Region of Yogyakarta is the community of Kalijeruk I and II Hamlets. This community has abundant cassava resources in its area because the hamlets still have many rice fields. However, the women in this community have not yet produced a variety of processed cassava products. Therefore, these women need to learn more about the different types of processed cassava products. A team of lecturers and students from the University of AKPRIND Indonesia carried out this community service activity. The activity was divided into several stages: first, socialization about the competition; second, the cooking contest; third, food presentation; fourth, food evaluation; and fifth, announcing the winners. This event provided the mothers with basic knowledge and motivation to create delicious, nutritious, and economically valuable cassava-based dishes. This was demonstrated by the 12 different cassava dishes prepared by the mothers.